99mTc-Sestamibi Thyroid Scintigraphy in Amiodarone-Induced Thyrotoxicosis: Functional Imaging–Histopathologic Correlation. (15th September 2022) - Wang, Ray; Better, Nathan; Sivaratnam, Dinesh; Westcott, James; Forehan, Simon; Christie, Michael; Pattison, David A.; Fourlanos, Spiros
Abstract: 99m Tc-sestamibi thyroid scintigraphy (STS) can aid in differentiating between types 1 and 2 amiodarone-induced thyrotoxicosis (AIT). We present a consecutive case series of 4 men (aged 56–75 years) in whom both 99m Tc-STS and thyroid histology were consistent with a diagnosis of type 2 AIT, representing the first reported histopathologic correlation for this diagnostic test. Median amiodarone treatment duration was 26 months (range, 10–39 months), and amiodarone was discontinued a median of 3 months preoperatively (range, 2–4 months) in all 4 cases. 99m Tc-STS is a promising functional imaging modality, which has the potential to aid clinicians in the diagnostic workup and treatment of AIT.